(untitled) (Psicologia USP, 2011)
Some rappers' irreverence and criticality and the happy erotic body swinging as proposed by funk, suggest a new scenario for Brazil's metropolis, where the youth art plurality comes up as a way to face the trace left by deep social fractures. The concepts of the "Dionysian vision of the world", "extreme aesthetics" and "revaluation of values", as defended by Nietzsche, and "eroticism", as conceived by Bataille, guided the method of "rupture of field", as defined by Herrmann. This one, essential to reconsider the notions of authority and tradition in the contemporary society, throughout the trends shown, particularly by rap and funk. Only ethnography of the regard which captures their irreverent erotic dimension - the "eroptica", according to Canevacci - seems to be able to identify in them an affirmative and critical aesthetics, as Nietzsche would say, able to produce a true reversal of values in our society.